2014
DOI: 10.1016/j.jinsphys.2014.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and physical stresses induce a short-term immune priming effect in Galleria mellonella larvae

Abstract: a b s t r a c tExposure of larvae of Galleria mellonella larvae to mild physical (i.e. shaking) or thermal stress for 24 h increased their ability to survive infection with Aspergillus fumigatus conidia however larvae stressed in a similar manner but incubated for 72 h prior to infection showed no elevation in their resistance to infection with A. fumigatus. Stressed larvae demonstrated an elevated haemocyte density 24 h after initiation of the stress event but this declined at 48 and 72 h. Larval proteins suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 44 publications
(44 reference statements)
2
24
0
Order By: Relevance
“…The present study provided proof that the G. mellonella experimental system is amenable to an extended temperature range from 5°C to 37°C. It is well-known that temperature affects G. mellonella immune response to pathogens; however, the relevant previous studies focused on the effects of pre-incubation periods as they related to the immune responses [28,29]. Importantly, the current study differs from earlier publication in that the larvae were maintained at room temperature until infection and were not placed at 5°C and 15°C until after infection.…”
Section: Resultsmentioning
confidence: 95%
“…The present study provided proof that the G. mellonella experimental system is amenable to an extended temperature range from 5°C to 37°C. It is well-known that temperature affects G. mellonella immune response to pathogens; however, the relevant previous studies focused on the effects of pre-incubation periods as they related to the immune responses [28,29]. Importantly, the current study differs from earlier publication in that the larvae were maintained at room temperature until infection and were not placed at 5°C and 15°C until after infection.…”
Section: Resultsmentioning
confidence: 95%
“…Silkworms and the greater wax moth larva can be used as animal infection models at 37°C (25)(26)(27), but their infection sensitivities to fungi are drastically increased at 37°C compared to that at a lower temperature (19,(28)(29)(30)(31). The increased infection sensitivity of these insects at 37°C is considered to be due to damage to the immune system at a high temperature (32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%
“…mellonella larvae show an increase in haemocyte density and elevated expression of prophenoloxidase and two antimicrobial peptides (Browne et al. ). However, little is known about the influence of stress on the immune system in the context of trans‐generational effects.…”
Section: Introductionmentioning
confidence: 99%
“…In Galleria mellonella, it is shown that mild physical and/or thermal stress leads to short-term immune priming, protecting the larvae against infection with Aspergillus fumigatus. Furthermore, treated G. mellonella larvae show an increase in haemocyte density and elevated expression of prophenoloxidase and two antimicrobial peptides (Browne et al 2014). However, little is known about the influence of stress on the immune system in the context of trans-generational effects.…”
Section: Introductionmentioning
confidence: 99%